Wavelet Methods With Discrete Cosine Transform For Peak-To-Average Power Ratio And Bit Error Rate Reduction In Orthogonal Frequency Division Multiplexing Systems - Lim, Yong Liang (2019)
Orthogonal Frequency Division Multiplexing (OFDM) is nowadays applied in wireless networks, Digital Subscriber Line Internet Access, 4G mobile communications, digital television and audio broadcasting. This system has been widely used in high data rate wireless communications systems. High transmission bit rate, high spectral efficiency and robustness to frequency fading channels are the benefit for the application of OFDM. However, there is a major drawback in OFDM systems which is high Peak-to-Average Power Ratio (PAPR). High PAPR will reduce the performance of OFDM. Several techniques has been proposed to reduce PAPR. In this study, two objectives are identified. The first objective is to implement the improved PAPR reduction technique based on DCT on wavelet method. Then, the second objective is to analyze the performance of the proposed method based on PAPR and BER. This study is divided into four stages, understand the concept of OFDM implementation of algorithm, obtaining results and analyzing the simulation results. The simulation results show that improved method of DCT wavelet can reduce PAPR to about 5.111dB (35% PAPR reduction improvement) for 1024 subcarriers by using 64-QAM modulation scheme. Besides that, the Bit Error Rate is calculated to investigate the performance of the system by comparing the number of bits received in errors and the number of bits transmitted. DCT-precoded Wavelet gives 30% of improvement of BER whereas DCT-Wavelet gives 34% of improvement of BER